SELF-KNOWLEDGE: AN IMPORTANT FACTOR FOR IMPROVING TEACHERS’ EMOTIONAL RESPONSIVENESS IN LIFELONG EDUCATION - Kusnere, Ilga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The quality of a teacher's professional activity is closely tied to personal growth. Personal growth, however, is influenced by self-knowledge (K. G. Jung 1994, 2001; Wilber 2010, 2013; Plotkin, 2020; Dispenza, 2015, 2016). Nowadays, there is a shift in the approaches of upbringing and educational work – from a child-focused approach to a child-centered one (OECD, 2019). Therefore, one of the currently relevant skills is getting to know oneself in order to cooperate more successfully with others and be able to accept real-life situations. The results obtained confirm that through the self-knowledge process, teachers get to experience their own personality growth. Categories such as empathy, attitude, and daringness are identified in personal growth.The research shows that by experiencing the procedural activities of self-knowledge with the help of “Get to know yourself!” method and methodological tool developed by the author, teachers improve their emotional responsiveness.The results of the study show that through the experiences gained in the self-knowledge process, teachers learn to integrate new models of action into their pedagogical activities. The aim of the study was to show the importance of self-knowledge in improving teachers' emotional responsiveness in lifelong education, by using the method "Get to know yourself!" developed by the author of the study.The objectives of the study were literature examination and evaluation and work with the target audience by using the author's method and methodological tool "Get to know yourself!".Methods: Literature studies, survey, observation.